Clinical and Inflammatory Characteristics of the Chinese APAC Cough Variant Asthma Cohort - Lai, Kefang; Zhan, Wenzhi; Wu, Feng; Zhang, Yunhui; Lin, Lin; Li, Wen; Yi, Fang; Jiang, Ziyu; Dai, Yuanrong; Li, Suyun; Lin, Jiangtao; Yuan, Yadong; et al. (Frontiers in Medicine, 2022)
Background: AtyPical Asthma in China (APAC) cohort is a multi-center prospective, observational cohort set-up to investigate the clinical, pathophysiological features, prognosis and mechanisms of cough variant asthma (CVA). Objectives: To present the characteristics of newly physician-diagnosed adults with CVA (n=328) compared to mild-moderate classic asthma (CA, n=206). Methods and Main Results: CVA subjects showed a higher proportion of female (67.1% vs 55.3%, P=0.0084), abnormal laryngopharyngeal sensations (71.0% vs 51.0%, P<0.0001) than CA, but presented with near normal spirometry and higher methacholine PD20-FEV1 values (4.2 [1.0, 8.6] vs 0.8 [0.4, 4.7], P<0.0001). Lower fractional exhaled nitric oxide (FENO) levels (38.5 [20.0, 71.8] vs 53.0 [28.5, 92.2], P=0.0019), blood eosinophil counts (0.2 [0.1, 0.4] vs 0.3 [0.2, 0.5], P=0.0014), and sputum eosinophils (2.2 [0.2, 7.9] vs 12.2 [2.0, 34.5], P<0.0001) were found in CVA. Despite lower total serum IgE levels in CVA, there was similar proportion of atopy in both groups. The prevalence of cough in CA was 86.4%, while CVA reported more severe cough on Visual Analogue Scale, Cough Evaluation Test and Leicester Cough Questionnaire, similar anxiety and depression scores but better asthma control scores as reflected by Asthma Control Test compared to CA. No correlation was found between cough assessment outcomes and sputum eosinophil count, blood eosinophil count, FENO, spirometry variables or PD20-FEV1. Conclusion: Cough variant asthma is distinctive from classic asthma in regard of clinical features, lung function and airway inflammation. Quality of life is badly impaired as well in spite of better asthma control scores.